Wholesale flat subduction of the Indian slab and northward mantle convective flow: Plateau growth and driving force of the India–Asia collision - Jincheng Ma; Xiaodong Song; Hans-Peter Bunge; Andreas Fichtner; You Tian (Proceedings of the National Academy of Sciences, 2025)
The tectonic evolution of the Tibetan Plateau has been influenced by continental collision and postcollisional convergence of Indian and Eurasian plates, both of which have undoubtedly imposed their imprints on the lithosphere and upper-mantle structures beneath the collision zone. However, the mode by which the Indian Plate has subducted beneath Tibet, and its driving forces, have been highly uncertain. Here, we present seismic evidence from a full-waveform tomographic model that reveals flat subduction of the Indian Plate beneath nearly the entire plateau at ∼ 300 km depth, implying that the slab may have transitioned to positive/neutral buoyancy and is no longer capable of supporting steep-angle deep subduction. The horizontal distance over which the flat slab slides northward increases from west (where it collides with the Tarim lithospheric keel) to east (where it has resided approximately north of the Songpan-Ganzi Fold Belt beyond the Qiangtang Block). The Asian lithosphere is subducting beneath northeastern Tibet without colliding with the Indian slab. The low-velocity zone, with a thickness of 50 to 110 km, sandwiched between the Tibetan crust and Indian slab, is positively correlated with the high-elevation, low-relief topography of Tibet, suggesting partial melting of the uppermost mantle that has facilitated the growth and flatness of the plateau by adding buoyant material to its base. We propose that deep mantle convective currents, traced to the Réunion plume and imaged as large-scale low-velocity anomalies from the upper mantle under the Indian Plate downward toward the uppermost lower mantle under the Baikal-Mongolia Plateau, are the primary force driving the ongoing India–Asia postcollisional convergence.